The making of the Samarco disaster from the perspective of risk - de Oliveira Penido, Marina; Peters Coelho, Tádzio; Magno, Lucas (Geografares, 2024)
This article discusses the Samarco disaster, seeking a reading based on the risk approach – specifically criticizing the technical-economic foundation of risk analysis and the business rationality of maximizing economic results and reducing costs – paying attention to legal transgressions of mining companies and the inoperability of the law. At the end of the article, we state that, more than the dimension of risk within the scope of the conditions leading to disasters around mining, it is necessary to question neo-extractivism as a privileged model of development. To prepare this article, we used relevant literature, analysis of legislation regarding dams used for waste disposal and technical reports produced on the rupture of the Fundão dam.